SPIRITUALITAS DAN PERSEPSI KESEHATAN LANSIA DENGAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS MAYANG JEMBER - Dewi*, Sofia Rhosma (Universitas Muhammadiyah Jember, 2016)
Conventional treatment of hypertension using medications are not always show positive outcome. Spirituality is expected to be a better solution in order to treat hypertension in elderly. This research is conducted to analyse the correlation of spirituality and health perception of elderly with hypertension in working area of Puskesmas Mayang. It?s a correlational research with cross sectional methode. The sample are 30 elderly with hypertension live in working area of Puskesmas Mayang and taken by sistematic random sampling. The data collected by using SAI for spirituality and SF 12 for elderly?s health perception then analyse using Pearson correlation. The result show p value 0,038 and 0,027 means that there are significant correlation between spirituality and elderly?s health perception. The nurse as a health practitioner are expected to pay attention to clients spirituality in order to enhance client?s outcome. Keywords : elderly, spirituality and hypertension